DEMOCRACIA E PARTICIPAÇÃO NO CONTEXTO LOCAL: análise do Orçamento Participativo de São Luís na gestão 2009-2012. - Lima, Tereza Dávila do Nascimento (2013)
This work aims to study the analysis of the Participatory Budget of São Luís using as reference the management 2009-2012. Discusses democratic theory based on classical authors, comparing representative and participatory models. Analyzes the peculiarities of the recent history of Brazilian democracy. Part to a resumption of the profile associative St. Louis, which has enabled the implementation of more participatory budget. Shows how the context of political disputes in which the OP was entered that stage.Try to understand the social and political variables that influenced the performance of the OP during the administration of João Castelo (PSDB). It appears that the Participatory Budgeting process continued to experience a decline in popular participation, this being due, in part, the lack of interest of the municipal administration. Some factors raised in the working state that the performance of PB in São Luís during the period 2009-2012, is given to reproduce the failures of previous administrations without contributing to effective participation. To carry out the work were made literature searches, we used some documentary sources and conducted semi-structured interviews with officials from the Secretary Extraordinary s Participatory Budgeting Secretary (SEMOP) responsible, during this period, through social mobilization